ANALISIS KOMPARASI DAYA SAING EKSPOR LADA INDONESIA TERHADAP VIETNAM DAN MALAYSIA DI PASAR ASEAN - Ariesha, Yurike; Alamsyah, Zulkifli; Malik, adlaida (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2019)
This research is aimed to: 1) determine the development of pepper export from Indonesia, Vietnam, and Malaysia in ASEAN market from 2000-2015, 2) analyze export competitiveness of pepper from Indonesia, Vietnam, and Malaysia in ASEAN market from 2000-2015, 3) analyze the difference of pepper export competitiveness from Indonesia and Vietnam in ASEAN market from 2000-2015, and 4) analyze the difference of pepper export competitiveness from Indonesia and Malaysia in ASEAN market from 2000-2015. Type of research used is descriptive quantitative. The research data are total export value and pepper export value from world to ASEAN, pepper export and import value of Indonesia, Vietnam and Malaysia, and total export value of Indonesia, Vietnam, and Malaysia in 2000-2015. The data used are obtained from the official website of Food and Agriculture Organization, United Nations Commodity Trade, Central Statistics Agency, and Directorate General of Estate Crops. The results of the comparison competitiveness of Indonesia and Vietnam pepper exports showed that significant result from RCA (0.73), ECI (0.88), CMS (Commodity Composite Effect) (0.62), CMS (Market Distribution Effect) (0.55), and CMS (Competitiveness Effect) (0.59) is greater than the value of Î± (0.05). Based on these calculations, it can be seen that there is no difference in comparative competitiveness, competitive competitiveness, commodity composition effect, market distribution effect, and competitiveness effect between Indonesia and Vietnam. However, the significant result of ISP (0.02) is smaller than the value of Î± (0.05) which means that difference in the position of competitiveness from Indonesia greater than Vietnam. The same is true for the comparison competitiveness of Indonesia and Malaysia pepper exports, but the value of significant is different from the comparations of Indonesia and Vietnam.